Stability, electronic structure and magnetic properties of vacancy and nonmetallic atom-doped buckled arsenene: first-principles study. Issue 49 (3rd May 2016) - Xu, Chunyan; Zhu, Mingfeng; Zheng, Huiling; Du, Xiaobo; Wang, Wenquan; Yan, Yu
Abstract : A doping C, Si, O and S can induce the magnetic moments of 1.0 μ B in buckled arsenene, while the substitutional doping of H, F, B, N and P can not produce the magnetism. Abstract : Using first-principles calculations, we systematically explore the influence of vacancies and a series of substitutional nonmetallic atoms, such as H, F, B, N, P, C, Si, O and S, on the geometrical structure, electronic structure and magnetic properties of buckled arsenene. The calculations show that compared to graphene and silicene, vacancies are more easily formed in buckled arsenene, and vacancy doped buckled arsenene is thermo-dynamically stable at room temperatures. Moreover, all the substitutionally doped buckled arsenene samples with nonmetallic atoms are stable. Remarkably, due to the formation of one nonbonding p electron of dopant C and Si or a neighboring As atom around O, Si and vacancies, a doping C, Si, O and S atom and a vacancy induce a magnetic moment of 1.0 μ B in buckled arsenene. Furthermore, it is found that the magnetic coupling between the moments induced by two C, Si, O and S are long-range anti-ferromagnetic, and the calculated DOS and the spin density distribution show that the p–p hybridization interaction involving polarized electrons is responsible for the magnetic coupling. Our results demonstrate that the magnetism of buckled arsenene can be effectively engineered by vacancies and the substitutional doping of some nonmetallic atoms.